Evaluating Esp Nursing Textbooks: Perspectives of Nursing Students on Language Learning Resources - Fitri Handayani; Mike Amelia (Journal of English Language Learning, 2024)
This study evaluates the effectiveness of two English for Specific Purposes (ESP) textbooks, used at the Health Polytechnic in Solok, Indonesia. The research aims to assess how well these textbooks align with the academic and professional needs of nursing students. A survey was conducted among 80 second-year nursing students enrolled in the English for Nursing course. Data was collected through a 19-item questionnaire covering five key dimensions: aims and approach, design and organization, language content, skills, and topics. The results revealed that students generally responded positively to the textbooks, highlighting their well-organized structure, relevant grammar coverage, and practical clinical scenarios. However, some areas were identified for improvement, particularly the coverage of pronunciation and writing activities. The lack of focus on these aspects could hinder students’ communication skills and documentation abilities, which are essential in medical settings. This study emphasizes the importance of refining textbook content to better support students' language development and professional preparation. Future research is encouraged to explore the long-term impact of these textbooks on students' language proficiency and to compare similar materials used internationally for further improvement.